Evidence for the Misfolding of the A1 Domain within Multimeric von Willebrand Factor in Type 2 von Willebrand Disease. Issue 2 (17th January 2020) - Tischer, Alexander; Brehm, Maria A.; Machha, Venkata R.; Moon-Tasson, Laurie; Benson, Linda M.; Nelton, Katelynn J.; Leger, Rachel R.; Obser, Tobias; Martinez-Vargas, Marina; Whitten, Steven T.; Chen, Dong; Pruthi, Rajiv K.; et al.
Abstract: Von Willebrand factor (VWF), an exceptionally large multimeric plasma glycoprotein, functions to initiate coagulation by agglutinating platelets in the blood stream to sites of vascular injury. This primary hemostatic function is perturbed in type 2 dysfunctional subtypes of von Willebrand disease (VWD) by mutations that alter the structure and function of the platelet GPIbα adhesive VWF A1 domains. The resulting amino acid substitutions cause local disorder and misfold the native structure of the isolated platelet GPIbα–adhesive A1 domain of VWF in both gain-of-function (type 2B) and loss-of-function (type 2M) phenotypes. These structural effects have not been explicitly observed in A1 domains of VWF multimers native to blood plasma. New mass spectrometry strategies are applied to resolve the structural effects of 2B and 2M mutations in VWF to verify the presence of A1 domain structural disorder in multimeric VWF harboring type 2 VWD mutations. Limited trypsinolysis mass spectrometry (LTMS) and hydrogen-deuterium exchange mass spectrometry (HXMS) are applied to wild-type and VWD variants of the single A1, A2, and A3 domains, an A1A2A3 tridomain fragment of VWF, plasmin-cleaved dimers of VWF, multimeric recombinant VWF, and normal VWF plasma concentrates. Comparatively, these methods show that mutations known to misfold the isolated A1 domain increase the rate of trypsinolysis and the extent of hydrogen-deuterium exchange in local secondary structures of A1 within multimeric VWF. VWD mutation effects are localized to the A1 domain without appreciably affecting the structure and dynamics of other VWF domains. The intrinsic dynamics of A1 observed in recombinant fragments of VWF are conserved in plasma-derived VWF. These studies reveal that structural disorder does occur in VWD variants of the A1 domain within multimeric VWF and provides strong support for VWF misfolding as a result of some, but not all, type 2 VWD variants. Graphical abstract: Image 1 Highlights: Mutations that misfold the vWF A1 domain have not been explicitly observed in multimeric VWF native to blood plasma. Two mass spectrometry methods are developed to detect disorder within the A1 domains of multimeric VWD variants of VWF. VWD mutations alter the structure of A1 without affecting other vWF domains, vWF multimerization, or cellular localization.